Pelvic organ prolapse surgery in Finland from 1987 to 2009: A national register based study. (July 2017) - Kurkijärvi, Kaisa; Aaltonen, Riikka; Gissler, Mika; Mäkinen, Juha
Abstract: Objectives: To establish the trends in pelvic floor surgery in Finnish female population and to evaluate the age-specific incidence as well as the lifetime risk for pelvic organ prolapse surgery. Study design: We conducted a population-based register study, which includes all Finnish women ( n = 77 906), who underwent surgery for pelvic organ prolapse in Finland 1987–2009. The women were identified in the Care Register for Health Care based on the procedure codes. Number of procedures, age-adjusted incidence, age-specific incidence, cumulative incidence, lifetime risk were calculated. Results: A total of 93 226 surgical procedures for POP were performed. The age-adjusted incidence of prolapse surgery was 1.3/1000 women in 1987. After that there was an increase which peaked in 1996 with 1.9/1000, and a decline thereafter back to 1.3/1000 in 2009. The lifetime risk for a woman to have undergone at least one surgical procedure for prolapse was 12.8%. Surgery was most common within women aged 70 to 79 years, followed by women aged 60 to 69 years. The most popular procedure until 1991 was cervix amputation with colporraphies, surpassed thereafter by colporraphies only or with combined vaginal hysterectomy. Conclusion: Surgery for pelvic organ prolapse is common and more than every tenth woman underwent such surgery during lifetime.